Potensi Wakaf dan Dana Abadi Akademik dalam Manajemen Keuangan Pendidikan Tinggi : Literature Review dengan Metode PRISMA - Azhari, Chika Amalia; Purwana, Dedi (Fakultas Ekonomi dan Bisnis Islam, 2024)
This study aims to explore the role of waqf management in addressing the challenges of increasing academic endowments, managing asset allocation in Higher Education Institutions in Indonesia. This research uses a literature review approach with the Systematic Literature Review PRISMA model. Data taken from existing literature and data on Waqf Management, Academic Endowment, Asset Allocation, Higher Education Institutions, Indonesia, especially waqf management in universities in Indonesia. This research potential of sharia-based university financial management as an alternative to overcome challenges and financial problems faced by universities in Indonesia. The findings show that financial planning based on the concept of Sharia Waqf stimulates the potential growth of higher education endowment funds in Indonesia. Several methods such as the use of cash waqf mechanisms, involving the Indonesian waqf movement institution as an part to socialize the waqf movement, accepting other assistance such as alms and grants, increasing the religiosity value of each academic staff at the university, utilizing blockchain applications as a tool to address accountability and transparency in waqf management at the university, increasing asset ownership,expanding the alumni network, designing appropriate investments with selected risks for each of university. While the literature review provides valuable insights, there is room for improvement, and further research could re-explorer alternative methods that are more effective and efficient. The complexity of financial management with waqf principles in higher education towards academic endowments and university asset allocation requires further analysis and review to uncover important aspects in the broader landscape of higher education budgeting and financing management. This research has practical implications, recommending experts to support the waqf implementation process in universities across Indonesia. It highlights the importance of Shariah-based financial planning as a viable solution for any higher education institution and suggests that ongoing research in this area can contribute to refining the implementation mechanism.